Environmentally-benign plant protection possibilities against domestic Monilinia spp. in organic apple and stone fruit orchards - Holb, Imre; Szabó, Zoltán; Drén, Gábor; Thurzó, Sándor; Racskó, József; Dani, Mária; Tornyai, Julianna; Nyéki, József (Acta Agraria Debreceniensis, 2005)
In this study, possibilities of environmental-friendly plant protection against domestical brwon rot species were summarized for oecological pome and stone fruit orchards. Symtomps of the two most important brown rot species (Monilinia fructigena (Aderh. & Ruhl.) Honey and Monilinia laxa (Aderh. & Ruhl.) Honey) were described and then cultivar susceptibility to brown rot was discussed. Furthermore, mechanical, agrotecnical, biological, and other control possibilities (stone powders, plant extracts and restricted chemical materials) were shown.